The potential of ingestible sensors combined with family involvement interventions for medication supervision in Tuberculosis patients: A literature review - Meidina, Adinda Nezma; Ramadhanti, Nafilah; Riza, M. Aidil Tarensyah; Dapala, Zelka; Fareza, M. Daffa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Tuberculosis (TB) is an airborne infectious disease that remains the second leading cause of death from infectious diseases globally. A major challenge in eliminating TB, despite it being preventable and curable, is the low adherence to treatment. This literature review aims to provide insights into the potential of ingestible sensors combined with family involvement interventions for medication supervision in TB patients, ensuring that medications are actually swallowed and addressing a key limitation of the previous DOT method. Methods: This study used a literature review method with the keywords